CGIAR hosts groundbreaking Alliance of Champions for Food Systems Transformation - Llano-Arias, Valeria (CGIAR System Organization, 2024)
The Alliance of Champions for Food Systems Transformation (ACF) was launched at Climate COP28 in response to various challenges in food systems, including record-breaking global temperatures, extreme weather events, and the urgent need to address climate change and food security. ACF seeks to accelerate global progress in five key areas: climate mitigation, food security and nutrition, adaptation and resilience, equity and livelihoods, and nature and biodiversity. These challenges have upended food systems worldwide, jeopardizing livelihoods and exacerbating food insecurity.